Modern aspects of treatment of reversible forms of pulpitis in permanent teeth with unformed roots - Bunyatyan, K. (Actual Dentistry, 2018)
Goal. Increasing the efficiency of treatment of reversible forms of pulpitis of permanent teeth with unformed roots. Patients and methods. Conduct basic and additional research methods in 36 children with reversible forms of pulpitis of the first permanent molars with unformed roots. Perform a vital amputation within a healthy pulp followed by tricalcium silicate cement coating. And also give a clinical justification for choosing a method of treatment using this material. The patients were divided into 2 groups. The first group consisted of 16 children with reversible forms of pulpitis of the first permanent molars, the roots of which were at the stage of root growth in length. The age group of these children was 6–7 years. The second group consisted of 20 children with reversible forms of pulpitis of the first permanent molars. The age of the children of the second group was 8–9 years, respectively, the roots of the first permanent molars were at the stage of the unformed apex. Results. As a result of research and application of tricalcium silicate cement, the clinical and radiological aspects characterizing the regenerative processes of permanent teeth with unformed roots showed themselves at different times depending on the stage of formation of the root system. Conclusions. 1. When treating the pathology of pulp of permanent teeth with unformed roots, tricalcium silicate is used, which has a pronounced effect on the physiological processes of apexogenesis and apexification. 2. The method of vital pulpotomy allows to maintain the viability of the root pulp by creating a calcified barrier (dentine bridge). 3. We established that, depending on the stage of formation of the root system, the regenerative processes (hard-tissue barrier) of immature pulp showed themselves at different times. 4. It was also found that the method of vital pulpotomy with subsequent coating with a material based on tricalcium silicate provides a high level of antiseptic (aseptic inflammation), resulting in the differentiation of fibroblasts and mesenchymal cells into odontoblasts. In the future, collagen fibers are formed, which subsequently mineralize into fibrodentin. Key words: children, permanent teeth with unformed roots, root growth in length, unformed apex, odontotropic action, dentine bridge, tricalcium silicate, apexogenesis, apexofication.